Intravenous delivery of autologous mesenchymal stem cells limits infarct size and improves left ventricular function in the infarcted porcine heart - Krause, Ulf; Harter, Christoph; Seckinger, Anja; Wolf, David Gregor; Reinhardt, Adrian; Bea, Florian; Dengler, Thomas; Hardt, Stefan; Ho, Anthony Dick; Katus, Hugo; Kücherer, Helmut; Hansen, Alexander E. W. (Stem Cells and Development, 2007)
Systemic delivery of bone marrow-derived mesenchymal stem cells (MSCs) is a noninvasive approach for myocardial repair. We aimed to test this strategy in a pig model of myocardial infarction. Pigs (n = 8) received autologous MSCs (1 x 106/kg body weight) labeled with fluorescent dye 48 h post proximal left anterior descending artery (LAD) occlusion. Hemodyamics, infarct size, and myocardial function were assessed at baseline and after 1 month. Morphologic analysis revealed that labeled MSCs migrated in the peri-infarct region, resulting in smaller infarct size (32 ± 7 vs. 19 ± 7%, p = 0.01), higher fractional area shortening (23 ± 3 vs. 34.0 ± 7%, p = 0.001), lower left ventricular end diastolic pressure (18.7 ± 5 vs. 10.2 ± 4 mmHg, p = 0.02) and higher +dp/dt (4,570 ± 540 vs. 6,742 ± 700 mmHg/s, p = 0.03) during inotropic stimulation. Systemic intravenous delivery of MSCs to pigs limits myocardial infarct size and is an attractive approach for tissue repair.
Gesehen am 26.10.2021